Pendugaan Umur Simpan Manisan Kering Jambu Biji dalam Kemasan Menggunakan Metode ASLT - Gokma Ampetua Siregar; Usman Ahmad; Leopold Oscar Nelwan (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2025)
Processing guava into dried candied is an alternative to extend the shelf life of guava. The purpose of this study was to estimate the shelf life of dried candied guava in polypropylene plastic packaging at any storage temperature. Through changes in the values of the quality parameters, the shelf life of candied guava at various storage temperatures was determined using the Accelerated Shelf Life Testing (ASLT) method of the Arrhenius model. Dried candied guava that had been packaged in polypropylene plastic packaging (0,08 mm thickness) and then was stored in an incubator with several storage temperatures, which are 35ºC, 40 ºC, 45 ºC, and 50ºC. Quality analysis was conducted on changes in water content, color value, and vitamin C. Estimation of the shelf life of the Arrhenius model is based on critical quality parameters, in this study the deterioration of vitamin C content is the critical parameter. The shelf life of dried candied guava in polypropylene plastic packaging when stored at 20˚C is 282 days, at 25˚C storage is 134 days, and storage at 30˚C lasts up to 65 days. Shelf life will increase if the dried candied guava is stored at a lower temperature and vice versa.